Axillary local anesthetic spread after the thoracic interfacial ultrasound block - a cadaveric and radiological evaluation - Torre,Patricia Alfaro de la (2017)
Abstract Background Oral opioid analgesics have been used for management of peri- and postoperative analgesia in patients undergoing axillary dissection. The axillary region is a difficult zone to block and does not have a specific regional anesthesia technique published that offers its adequate blockade. Methods After institutional review board approval, anatomic and radiological studies were conducted to determine the deposition and spread of methylene blue and local anesthetic injected respectively into the axilla via the thoracic inter-fascial plane. Magnetic Resonance Imaging studies were then conducted in 15 of 34 patients scheduled for unilateral breast surgery that entailed any of the following: axillary clearance, sentinel node biopsy, axillary node biopsy, or supernumerary breasts, to ascertain the deposition and time course of spread of solution within the thoracic interfascial plane in vivo. Results Radiological and cadaveric studies showed that the injection of local anesthetic and methylene blue via the thoracic inter-fascial plane, using ultrasound guide technique, results in reliable deposition into the axilla. In patients, the injection of the local anesthetic produced a reliable axillary sensory block. This finding was supported by Magnetic Resonance Imaging studies that showed hyper-intense signals in the axillary region. Conclusions These findings define the anatomic characteristics of the thoracic interfascial plane nerve block in the axillary region, and underline the clinical potential of this novel nerve block.